Quality of life of geriatric cancer patients undergoing chemotherapy in Hospital Universiti Sains Malaysia (Hospital USM) - Zainol, Ain Nur Afini (Universiti Sains Malaysia, 2016)
Quality of Life issue has historically played an important part in the nursing role of patient advocacy. Quality of Life differs for each individual and is dependent on different factors such as socio-demographic data and clinical data. Mostly, previous study that review on quality of life of cancer patients undergoing chemotherapy cover all the different age groups, and older patients tend to be underrepresented. A crosssectional survey design was used to determine quality of life of geriatric cancer patients at hospital USM. 57 respondents were recruited through the purposive sampling method. Because this study involving vulnerable population, the questionnaire was answered by respondents with guided by researcher and fitness status of the respondents was judged first by the researcher using KPS score. Data was statistically analyzed using the software package SPSS version 22.0. Statistical significance was considered at p value <0.05. The findings showed that most of the geriatric (86.0%) experienced moderate impairment in their Quality of Life with the most effected domain is physical well-being (mean= 10.46) followed by functional well-being. While emotional and social well-being was less affected. Besides that, chisquare test showed that there is no significant association between geriatrics' sociodemographic variables with Quality of Life's outcomes which are vice versa with clinical variables. In conclusion, since only clinical variables have significant association with Quality of Life outcomes, the further research should be done to determine the socio-demographic factors that contribute significantly to geriatric cancer patients' Quality of Life. This will help to improve health services and Quality of Life of geriatric.